JURIDICAL REVIEW OF THE CRIMINAL ACTION OF SPREADING PORNOGRAPHY CONTENT ( STUDY OF DECISION NUMBER: 2661/ Pid.Sus /2020 /PN. Mdn): TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENYEBARAN KONTEN PORNOGRAFI ( STUDI PUTUSAN NOMOR: 2661/ Pid.Sus /2020 /PN. Mdn) - Al Putra Jaya Sihura, Emanuel (LPPM UPMI, 2023)
Criminal Law is a public law used to limit human behavior to maintain public order. In enforcing the law conducted by the government and the authorized parties, it is regulated by laws and regulations. Accountability in criminal law can be interpreted as criminal liability, in Dutch torekenbaarheid, in English criminal responsibility or criminal liability. Criminal liability is punishing the maker for an act that violates a prohibition or creates a prohibited condition. In this problem, the author included several formulations of the problem, namely how the regulate criminal law against perpetrators of spreading porn videos was, and how the criminal liability against the perpetrators of spreading porn videos base on decision number 2661/Pid.Sus/2020/PN Mdn was. Through the anti-pornography law, it can be interpreted the difference in the interpretation of various pornography, so that the problem can be solved. In this study, the author used the type of normative legal research. It is research conducted by examining library materials (secondary data) or library law research. Social media is an online medium, with its users being able to easily participate, share, and create content, namely blogs, social networks, wikis, forums, and virtual worlds. The most common forms of social media used by people around the world are Blogs, social networks, and wikis. The criminal law regulation for the perpetrators of spreading porn videos was regulated in Law No. 44 of 2008 concerning Pornography Article 29 paragraph (1) and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions 2. Thus, criminal liability for perpetrators of spreading porn videos crime (Study of Decision Number 2661/Pid.Sus/2020/PN.Mdn) was appropriate because it met subjective elements.